1999
DOI: 10.1136/oem.56.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Mortality patterns among workers exposed to acrylamide: 1994 follow up.

Abstract: Objective-To update the mortality experience of a cohort of 8508 workers with potential exposure to acrylamide at three plants in the United States from 1984-94. Methods-Analyses of standardised mortality ratios (SMR) with national and local rates and relative risk (RR) regression modelling were performed to assess site specific cancer risks by demographic and work history factors, and exposure indicators for acrylamide and muriatic acid. Results-For the 1925-94 study period, excess and deficit overall mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 9 publications
2
79
2
5
Order By: Relevance
“…In a study which was performed with 371 workers exposed to acrylamide by means of organic dyes, it was determined that the rate of death occurred as a result of especially digestion and respiration system cancers was more than expected [42]. In another study carried out with 8500 workers exposed to acrylamide due to their jobs, it was suggested that there was an increase in thyroid cancer and pancreas cancer depending on the exposure dosage [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a study which was performed with 371 workers exposed to acrylamide by means of organic dyes, it was determined that the rate of death occurred as a result of especially digestion and respiration system cancers was more than expected [42]. In another study carried out with 8500 workers exposed to acrylamide due to their jobs, it was suggested that there was an increase in thyroid cancer and pancreas cancer depending on the exposure dosage [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort of 371 workers exposed to acrylamide through organic dyes, cancer mortality was higher than expected, mainly because of deaths from cancer of the digestive tract and respiratory system (Sobel et al, 1986). More recently, Marsh et al (1999) in a cohort of 8500 workers with potential occupational exposure found little evidence for an excess risk of cancer mortality overall. While an excess of thyroid cancer and a doseexposure relation with pancreatic cancer were suggested, the wide CIs precluded definitive assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown positive dose-response relationships between acrylamide given in drinking water and cancer in multiple organs in both mice and rats (9)(10)(11)(12), among which were several hormone-sensitive organs, such as the mammary glands and the uterus. However, studies on humans with occupational acrylamide exposure have been negative thus far, apart from an increased risk of pancreatic cancer, but this was based on a small number of cases (13)(14)(15)(16)(17)(18). Dietary acrylamide intake and its relation with various types of cancer have been studied in a few case-control studies (19)(20)(21) and only two prospective cohort studies on breast and colorectal cancer (22,23).…”
Section: Introductionmentioning
confidence: 99%